Risk Factors for Birth Asphyxia in Hospital-Delivered Newborns in Dodoma, Tanzania: A Case-Control Study - Laidi S. Msisiri MSc; Stephen M. Kibusi MA, PhD; Franisca D. Kimaro MMED (SAGE Publishing, 2024)
Introduction Asphyxia at birth remains the leading cause of neonatal morbidity and mortality worldwide, accounting for ∼23% of all neonatal deaths. Although the causes vary from country to country, early identification and treatment of risk factors can improve the situation. Objectives To determine the risk factors of birth asphyxia in hospital-delivered neonates in Dodoma, Tanzania. Methods A matched case-control study was conducted from May to July 2017 at Dodoma Region Referral Hospital. Data were collected using a semistructured questionnaire and a standard antenatal care index card. Cases were neonates diagnosed with asphyxia at birth ( N   =  100), while controls were neonates not diagnosed with asphyxia at birth ( N   =  300). A binary logistic regression model was used to assess the independent variables associated with birth asphyxia and reported as crude and adjusted odds ratios along with their 95% confidence intervals. Results A total of 400 newborns and their birth mothers were involved in the study. The average age of the case mothers was 26.9 years ( SD   =  7.85) and that of the control mothers was 27.24 years ( SD   =  6.08). Place of residence, anemia, maternal age, prenatal visits attended, use of herbs during labor, previously complicated pregnancy, duration of labor, meconium-stained amniotic fluid, and mode of delivery were predictors of birth asphyxia. Conclusion The study showed that most predictors of birth asphyxia can be prevented. The results suggest appropriate health education before conception, effective follow-up through prenatal care, early identification and treatment of high-risk pregnant women, and proper monitoring of labor and delivery.